Intelligent travel information platform based on location base services to predict user travel behavior from user-generated GPS traces. Issue 3 (3rd July 2017) - Arain, Qasim Ali; Memon, Hina; Memon, Imran; Memon, Muhammad Hammad; Shaikh, Riaz Ahmed; Mangi, Farman Ali
Abstract: In recent past, social networking has received great attention and millions of geo tagged photos are placed online on different social networks websites like flicker, Facebook and Instagram. According to this, people used to share their photos and share their travel experience over social media. However, photos themselves has a lot of hidden information to share like position, time etc. We presented a new technique related to location travel for tourist by looking on to their time and preference needs. We used to acquire its preference based on his or her past time in one city and based on this information recommend another city. We executed certain experiments to support our technique and acquire data-set from publically available flicker database. Simulation results have revealed that our travel recommendation system has been devised according to user needs and outperformed other previous travel and recommendation methods.